Decision Support System for Selecting Media Online Journalist in Reporting on DPRD DKI Jakarta Using Analytical Hierarchy Process (AHP) - Yuyun Yuningsih - Universitas Nusa Mandiri; Ari Puspita; Hilda Amalia; Ade Fitria Lestari - Universitas BSI (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2022)
Abstract - The presence of online media adds to the splendor of the press in Indonesia, providing the fastest information needed by the wider community, and faster than print media. The current problem with the DKI Jakarta DPRD is that there are many online media journalists who provide information to the public that does not match the facts. When the news is covered, either from the commission meeting or during direct interviews with DPRD members. However, there are also journalists who prioritize good journalism ethics in covering and reporting on it. It will be very interesting, if DPRD Members select the best online media journalists, to give awards to fellow journalists, so that they can provide a complete picture in presenting the news and during the reporting process. Decision Support System is part of an information system based on computer technology. The decision support system has several stages, namely being able to define the problem, collect relevant data, processing data that will become information, so that it can determine a very objective assessment. The method used in making decisions on the selection of the best online media journalists is the Analytical Hierarchy Process (AHP). After doing the testing, the final result obtained from this research is that RRI journalists are selected in first place with a score of 51%, then in second place are Warta Kota journalists with a score of 28% and in third position are Harian Terbit journalists with a score of 21%.Keywords: Best Journalist, Online Media, Analytical Hierarchy Process, DPRD DKI Jakarta Province. Abstrak - Kehadiran media online menambah semaraknya dunia pers di Indonesia, memberikan informasi tercepat yang dibutuhkan oleh masyarakat luas, dan lebih cepat dibandingkan dengan media cetak. Permasalahan yang terjadi saat ini pada DPRD DKI Jakarta adalah banyak para jurnalis media online yang memberikan informasi kepada masyarakat yang kurang sesuai fakta yang ada. Pada saat berita dilipu, baik dari saat rapat komisi maupun pada saat wawancara secara langsung dengan Anggota DPRD. Akan tetapi ada juga jurnalis yang lebih mengedepankan etika jurnalisme yang baik dalam meliput dan memberitakannya. Akan menjadi hal yang sangat menarik, apabila Anggota DPRD melakukan pemilihan jurnalis media online terbaik, untuk memberikan penghargaan kepada rekan-rekan jurnalis, sehingga mereka dapat memberikan gambaran yang utuh dalam menajikan berita serta pada saaat proses peliputannya. Sistem Pendukung Keputusan merupakan bagian dari sistem informasi yang berbasis teknologi komputer. sistem pendukung keputusan memiliki beberapa tahapan yaitu dapat mendefinisikan masalah, mengumpulkan data yang relevan, pengolahan data yang akan menjadi informasi, sehingga dapat menentukan penilaian yang sangat objektif. Metode yang digunakan dalam pengambilan keputusan pada pemilihan jurnalis media online terbaik adalah Analytical Hierarchy Process (AHP). Setelah melakukan pengujian maka hasil akhir yang diperoleh dari penelitian ini yaitu terpilihlah jurnalis RRI di peringkat pertama dengan skor 51%, kemudian di posisi kedua jurnalis Warta Kota dengan skor 28% dan di posisi ketiga jurnalis Harian Terbit dengan skor 21%.Kata Kunci: Jurnalis Terbaik, Decision Support System, Analytical Hierarchy Process,